The impact of market timing on Canadian and US firms' capital structure - Zhaoxia Xu (Bank of Canada, 2009)
This paper studies the impact of market timing on Canadian firms' capital structure and makes a comparison with U.S. firms. There is no evidence that market timing affects Canadian firms' capital structure in the same manner as it affects their U.S. counterparts. The effect of past equity issues on Canadian firms' capital structure is transitory. Canadian firms adjust at a faster rate toward the leverage target than U.S. firms. These results challenge the generality of the markettiming theory of capital structure.
Keywords: G32; 330; Financial markets; International topics; Unternehmensfinanzierung; Kapitalstruktur; Eigenkapital; Kanada; USA